Characterisation for functional compounds of Italian oat genotypes - Sgrulletta, Daniela; Stefanis, Ester De; Conciatori, Andrea; Longoni, Cristina; Redaelli, Rita (MTT, 2004)
Functional foods are defined as foods which give physiological benefits beyond simple nutrition: they enhance overall health, help prevention or treatment of a disease, improve physical and mental performance, via an added functional ingredient (Jones 2002). As regards oats, an health claim was advanced in 1997, when FDA recognised the positive role of oat soluble fibre in reducing the risk of coronary heart disease, by lowering the level of serum cholesterol. Due to their high content of unsaturated lipids and protein of good biological value (rich in essential amino acids), oats represent therefore a raw material to be considered for the production of dietetic foods. An oat-wheat alimentary pasta was recently produced in Italy, using a reduced number of oat genotypes as sources of oat flour. In Italy, oat breeding programs are quite recent, being started about 20 years ago; breeding programs for naked oats are even more recent and rather limited. In addition, the available genetic variability for molecules acting as functional compounds (e.g. oat soluble fibre, â-glucan) has been poorly explored. In this study a group of naked oat cultivars from different countries and Italian breeding lines were characterised in terms of the main compounds related to nutritional quality: protein, soluble and insoluble â-glucan. Grain protein content ranged from 16.4% (BD126 and BD127, two Italian breeding lines) to 22.7 % d.m. (breeding line Se l84); the mean value was 19.2 ± 1.8 % d.m. The variation of â-glucan content was from 2.67 to 5.40 %d.m. and the mean value was 3,93 + 0.6 % d.m. Data showed also an high variability in relation to â-glucan composition (soluble and insoluble fraction). The results of two years of multiplication allowed to evidence significant genotype x year interactions for the functional components considered, in particular for total â-glucan. Finally, the water-soluble fraction of protein (albumins and globulins) was quantified in these genotypes. Jones, P.J. 2002. Clinical nutrition: 7.Functional foods more than just nutrition. CMAJ 1666(12): 1553-63.
Keywords: Ka; â-glucan; naked oats; Italian genotypes; functional compounds; variability